Microbial profiling during anaerobic digestion of cheese whey in reactors operated at different conditions. (March 2019) - Treu, Laura; Tsapekos, Panagiotis; Peprah, Maria; Campanaro, Stefano; Giacomini, Alessio; Corich, Viviana; Kougias, Panagiotis G.; Angelidaki, Irini
Graphical abstract: Highlights: Mesophilic and thermophilic anaerobic degradation of cheese whey was studied. Mono-digestion of whey led to accumulation of intermediates inhibiting the process. Co-digestion of whey with cattle manure can alleviate acidification incidents. The microbial profile of reactors was correlated with biochemical parameters. Abstract: This study investigates the efficiency in methane production of lab-scale mesophilic (37 °C) and thermophilic (54 °C) continuous stirred tank reactors fed with cheese whey at different operational conditions. Results showed that whey mono-digestion was feasible at mesophilic conditions, while at thermophilic conditions frequent acidification incidents were recorded. The limited buffer capacity of the influent feedstock was responsible for the unstable anaerobic digestion process. The co-digestion of cheese whey with cattle manure maintained the pH levels higher than 7.0, and therefore, stable methane production rates were achieved without any significant accumulation of volatile fatty acids. An additional enhancement of the methane productivity was achieved by in-situ H2 dispersion. Microbial community composition was investigated using high-throughput 16S rRNA gene amplicon sequencing and results were correlated with process parameters. Hydrogenotrophic methanogens were the dominant archaea during the whole experiment at mesophilic and thermophilic conditions.